Species distribution and antifungal susceptibility profile of Candida spp. bloodstream isolates from Latin American hospitals - Patrício Godoy; Iris Nora Tiraboschi; Luiz Carlos Severo; Beatriz Bustamante; Belinda Calvo; Leila Paula de Almeida; Daniel Archimedes da Matta; Arnaldo Lopes Colombo (Memorias do Instituto Oswaldo Cruz, 2003)
From March 1999 to March 2000, we conducted a prospective multicenter study of candidemia involving five tertiary care hospitals from four countries in Latin America. Yeast isolates were identified by classical methods and the antifungal susceptibility profile was determined according to the National Committee for Clinical Laboratory Standards microbroth assay method. During a 12 month-period we were able to collect a total of 103 bloodstream isolates of Candida spp. C. albicans was the most frequently isolated species accounting for 42% of all isolates. Non-albicans Candida species strains accounted for 58% of all episodes of candidemia and were mostly represented by C. tropicalis (24.2%) and C. parapsilosis (21.3%). It is noteworthy that we were able to identify two cases of C. lusitaniae from different institutions. In our casuistic, non-albicans Candida species isolates related to candidemic episodes were susceptible to fluconazole. Continuously surveillance programs are needed in order to identify possible changes in the species distribution and antifungal susceptibility patterns of yeasts that may occurs after increasing the use of azoles in Latin American hospitals.